Detection of Koi Herpesvirus (KHV) and Carp Oedema Virus (CEV) in Invasive Round Goby, Neogobius Melanostomus Pallas, 1814, from Poland and Germany - Jin, Yeonhwa (J Vet Res, 2020)
INTRODUCTION: The aim of the study was to determine the transmission potential of carp edema virus (CEV) and koi herpesvirus (KHV) introduced to Europe by the invasive round goby (Neogobius melanostomus). MATERIAL AND METHODS: A total of 70 round goby specimens were collected from the Szczecin Lagoon, Poland, and locations in Germany in the third and fourth quarters of 2018. The fish were analysed to detect KHV and CEV by PCR. RESULTS: Six fish specimens were positive for the presence of KHV, while none of the gobies examined showed the presence of CEV. CONCLUSION: The CEV genome was detected in the goby specimens from Germany and from Poland. Considering the high pace of the spread of the round goby and its effectiveness in acquisition of new ecological niches, it should be kept out during refilling of carp ponds. Further studies should focus on experimental cohabitation of CEV-infected round gobies and specific-pathogen-free (SPF) carp to investigate the potential for active virus transfer.